Taxus baccata intoxication: the sun after the electrical storm - Pinto, Alexandre (Rev Bras Ter Intensiva, 2021)
European yew (Taxus baccata) is a tree with alternate branchlets, green needles and reddish-brown bark. A high-dose ingestion of Taxus baccata for suicidal purposes usually results in death. The systemic toxicity is mainly cardiac. The authors describe the case of a young patient who ingested a high dose of yew needles and presented to the emergency department with a serious intoxication, which manifested as a chaotic malignant arrhythmia that was successfully treated after exhaustive supportive care.